PENGARUH CELEBRITY ENDORSER, BRAND IMAGE, DAN BRAND TRUST TERHADAP MINAT BELI PADA COFFESHOP RUANG BEBAS KOPI DI DENPASAR - Kadek Riza Nevilia; I Gusti Ngurah Agung Eka Teja Kusuma; Ni Putu Cempaka Dharmadewi Atmaja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Purchase intention (purchase intention) is the desire that arises in consumers towards a product as a result of a process of observing and learning consumers about a product. The factors that support buying interest are consumer interest in buying influenced by several factors, namely celebrity endorsers, brand image and brand trust on buying interest at Coffeshop Ruang Gratis Kopi in Denpasar. The location of this research is located at Jalan WR. Supratman no. 236, Kesiman Petilan, Denpasar, with the object of this study measuring celebrity endorsers, brand image and brand trust on buying interest at Coffeshop Ruang Gratis Kopi in Denpasar. The population in this study were consumers of the Coffee Free Space Coffeshop in Denpasar whose number is not known for certain, with a total sample of 100 respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of the study show that celebrity endorsers have a positive and significant effect on purchase intention at the Coffee Free Room Coffeshop in Denpasar, Brand image has a positive and significant effect on purchase intention at the Coffee Free Space Coffeshop in Denpasar, Brand trust has a positive and significant effect on Purchase intention at the Coffeshop Coffee Free Space In Denpasar. It is hoped that future researchers will not stick to the factors in this study, namely celebrity endorsers, brand trust and brand image, but can add other factors that might influence purchase intention.